Mos1 Mutagenesis Reveals a Diversity of Mechanisms Affecting Response of Caenorhabditis elegans to the Bacterial Pathogen Microbacterium nematophilum - Yook, Karen (Copyright © 2007 by the Genetics Society of America, 2007)
A specific host–pathogen interaction exists between Caenorhabditis elegans and the gram-positive bacterium Microbacterium nematophilum. This bacterium is able to colonize the rectum of susceptible worms and induces a defensive tail-swelling response in the host. Previous mutant screens have identified multiple loci that affect this interaction. Some of these loci correspond to known genes, but many bus genes [those with a bacterially unswollen (Bus) mutant phenotype] have yet to be cloned. We employed Mos1 transposon mutagenesis as a means of more rapidly cloning bus genes and identifying new mutants with altered pathogen response. This approach revealed new infection-related roles for two well-characterized and much-studied genes, egl-8 and tax-4. It also allowed the cloning of a known bus gene, bus-17, which encodes a predicted galactosyltransferase, and of a new bus gene, bus-19, which encodes a novel, albeit ancient, protein. The results illustrate advantages and disadvantages of Mos1 transposon mutagenesis in this system.